2015
DOI: 10.1093/nar/gkv1212
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for RNA-genome recognition during bacteriophage Qβ replication

Abstract: Upon infection of Escherichia coli by bacteriophage Qβ, the virus-encoded β-subunit recruits host translation elongation factors EF-Tu and EF-Ts and ribosomal protein S1 to form the Qβ replicase holoenzyme complex, which is responsible for amplifying the Qβ (+)-RNA genome. Here, we use X-ray crystallography, NMR spectroscopy, as well as sequence conservation, surface electrostatic potential and mutational analyses to decipher the roles of the β-subunit and the first two oligonucleotide-oligosaccharide-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…During infection in bacteria, Qb recruits the host-cell ribosomal S1 protein, which is composed of six oligonucleotide-oligosaccharide-binding (OB) domains, to initiate viral replication (Wahba et al, 1974). Two of these domains, OB1 and OB2, contact the Qb replicase core but use different motifs to contact discrete regions and wrap around the replicase core (Gytz et al, 2015;Takeshita et al, 2014). Thus, although the structure of S1 and P share no homology, the modular domains of S1 and three of the monomers of P contact similar regions on the finger subdomain of their respective RdRp using a similar strategy ( Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…During infection in bacteria, Qb recruits the host-cell ribosomal S1 protein, which is composed of six oligonucleotide-oligosaccharide-binding (OB) domains, to initiate viral replication (Wahba et al, 1974). Two of these domains, OB1 and OB2, contact the Qb replicase core but use different motifs to contact discrete regions and wrap around the replicase core (Gytz et al, 2015;Takeshita et al, 2014). Thus, although the structure of S1 and P share no homology, the modular domains of S1 and three of the monomers of P contact similar regions on the finger subdomain of their respective RdRp using a similar strategy ( Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…single-particle cryo-EM | ssRNA virus | genome packaging | maturation protein | lysis protein S ingle-stranded RNA (ssRNA) viruses infect all domains of life and are important pathogens (1)(2)(3)(4). Bacteriophages or phages, especially the canonical Leviviridae Qβ and MS2, have been model systems for studying ssRNA viral gene regulation (5)(6)(7)(8), genome replication (9,10), and encapsidation (11)(12)(13)(14). They have a near-icosahedral capsid, encapsidating genomic RNAs (gRNAs) of ∼3,500-4,300 nucleotides.…”
mentioning
confidence: 99%
“…An analysis of the amino acid sequence [ 6 ] has led to the conclusion that there are six OB domains in protein S1 ( Figure ). Subsequent structural studies have confirmed this conclusion with further refinement: the N-terminal OB domain (OB 1 ) contains 4 rather than 5 β-strands [ 10 , 16 - 18 ].…”
Section: Domain Structure Of Protein S1mentioning
confidence: 98%
“…At the same time, it was thought that the domains OB1 and OB2 do not bind RNA and are involved in the protein-protein interactions responsible for the binding of protein S1 to the ribosome and to the Qβ replicase core [ 1 ]. Recent studies have demonstrated that the OB1 and OB2 domains indeed form contacts with the Qβ replicase core [ 17 , 18 ], but, in addition, domain OB2 can interact with RNA due to the high density of positively charged residues on the surface area not involved in the protein-protein interaction [ 18 ]. Thus, all five classical OB domains of S1 possess RNA-binding properties.…”
Section: Domain Structure Of Protein S1mentioning
confidence: 99%